Déconstruire la recherche en éducation en contextes de racialisation : Débusquer le racisme épistémologique - Thésée, Gina (Canadian Journal of Education/Revue canadienne de l’éducation, 2021)
Taking into account the International Decade for People of African Descent (2015–2024; ID-PAD) declared by the UN, and through media coverage in 2020 on a global scale of anti-black racist events, the author of this article has chosen to address “the educational success of African Canadians,” the theme of this special issue of the Canadian Journal of Education, by presenting Canada and Quebec as contexts of racialization, and not only as contexts of immigration. The contexts of racialization and, their corollary, eco-systemic, systematic and chronic racism constitute life paths made up of obstacles and ruptures related to the justice, development and recognition of people of African descent, the central themes of the ID-PAD. In Canada, including in French-speaking Quebec, the academic paths of PAD (African-Canadian people), from preschool to university, turn out to be real obstacles that lead them to stumble, to doubt, to fail. Paradoxically, their success is accompanied by self-doubt, self-shame, withdrawal into oneself, conformity to the hegemonic system, and acceptance of their own muzzling; the fight against systemic racism is, thus, often avoided for fear of the consequences. This is miseducation and institutional racism. In this context, how to approach the notion of “educational success” of PAD in Canada and in French-speaking Quebec? Based on critical racial theory, this article proposes a theoretical-conceptual reflection that principally concerns educational research by highlighting epistemological racism as a dimension of systemic racism at work in research and teaching. Keywords: context of racialization, International Decade for People of African Descent, miseducation, iceberg of racism, epistemological racism, emancipatory education, transformative education